New Index to Characterize Ionospheric Irregularity Distribution - Endawoke Yizengaw (Space Weather)
Abstract Characterization of the global ionospheric irregularities as a function of local time, longitude, altitude, and magnetic activities is still a challenge for radio frequency operations, especially at the low‐latitude region. One of the main reasons is lack of observations due to the unevenly distributed instruments. To overcome this constraint, we developed a new spatial density gradient index (DGRI) at two different scale sizes: small scale and medium/large scale. The DGRI is derived from in situ density measurements onboard recently launched constellation of low‐Earth‐orbiting satellites (COSMIC‐2 and ICON) at the rate of 1 Hz. Hence, the DGRI appeared to be suitable parameter that can be used as a proxy to describe the essential features of ionospheric disturbances that may critically affect our radio wave application as well as to identify the “all clear” zone as a function of longitude, latitude, and local time—at a refreshment rate of 30 min or less.